The place of the rural normalist students in the corporate policy of the cardenist government (Tzintzun, Revista de Estudios Históricos, 2020)
The article has the purpose of explaining the place that rural â€œnormalistaâ€ students, organized in the Federation of Farmworker Students of Mexico (FECSM), had in the corporate policy of the government of Lázaro Cárdenas (1934-1940), a little explored aspect of that government that was so decisive in Mexican political history of the twentieth century.